Achievement of target blood pressure among community residents with hypertension and factors associated with therapeutic failure in the northern territory of Japan. Issue 10 (October 2022) - Yokokawa, Hirohide; Suzuki, Mai; Aoki, Nozomi; Sato, Yuki; Naito, Toshio
Objective: This study aimed to determine the rate of achieving the target blood pressure (BP) defined by Japanese hypertension management guidelines and to examine factors associated with achieving the target BP. Methods: This cross-sectional study, which was conducted between January 2012 and December 2015, examined the BP control status and associated factors among 9, 016 Japanese community residents with hypertension. Residents were divided into the following six groups: G1, young, middle-aged, and early-phase elderly patients; G2, patients with cerebrovascular disease; G3, patients with coronary artery disease; G4, patients with chronic kidney disease with proteinuria; G5, patients with diabetes; and G6, patients with chronic kidney disease without proteinuria. BP target achievement rates were calculated for each group. A multivariate analysis identified factors associated with "therapeutic failure" of target BP. Results: The target BP was achieved by 52.6% participants in G1, 84.3% in G2, 50.6% in G3, 45.6% in G4, 48.7% in G5, and 75.0% in G6. The body mass index and receiving antilipidemic medication were associated with therapeutic failure. Conclusion: This study shows that achievement rates for treatment goals among Japanese patients with hypertension are still low. Body mass index and treatment of dyslipidemia may be associated with the control of BP.